Wednesday

April 16, 2014

April 16, 2014

Posted by **Anonymous** on Sunday, January 20, 2013 at 11:27pm.

- Math -
**Anonymous**, Sunday, January 20, 2013 at 11:27pmX^2***

- Math -
**Reiny**, Monday, January 21, 2013 at 9:08amIt is true when f(x) and g(x) are inverses of each other, that is,

f(g(x)) = g(f(x)) = x

for f(x) = x^2 + x – 2 and g(x) = x + 4, since x+4 is clearly not the inverse of f(x) fog ≠ gof

**Related Questions**

Algebra - If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (...

Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...

college algebra - 1. answer the following for the given quadratic function f(x)=...

calculus - when working with composite functions, does fog=gof? how do i create ...

math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5

math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5

Math - Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show ...

Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.

Algebra 2 - If f(x) = x-3 g(x) = 2x+5 find fog and gof

Math - Find (fog)(2) f(x)=Squareroot 4-x; g(x)=1-3x^2 Find (gof)(-2) for the ...